If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -3 = 10x + -9 Reorder the terms: -3 + 2x = 10x + -9 Reorder the terms: -3 + 2x = -9 + 10x Solving -3 + 2x = -9 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -3 + 2x + -10x = -9 + 10x + -10x Combine like terms: 2x + -10x = -8x -3 + -8x = -9 + 10x + -10x Combine like terms: 10x + -10x = 0 -3 + -8x = -9 + 0 -3 + -8x = -9 Add '3' to each side of the equation. -3 + 3 + -8x = -9 + 3 Combine like terms: -3 + 3 = 0 0 + -8x = -9 + 3 -8x = -9 + 3 Combine like terms: -9 + 3 = -6 -8x = -6 Divide each side by '-8'. x = 0.75 Simplifying x = 0.75
| (y-3)^2/3=(10y-54)^1/3 | | 9/m | | 7(2+x)=21 | | 0.10x+0.05(4-x)=0.10(-1) | | (3x+7)=(5x-17) | | 4(2x+2)=25 | | 12y-4=-9 | | (x^2-1/5x)*(6x/x-1) | | 8x+11=12x-7 | | -5=4(2+9r)-5r | | 0.13y+0.08(y+9000)=2400 | | 4(-6p+2)=9p-1 | | -t+4=13 | | 4a+5=35 | | 5ln(x+4)-17=8 | | 12ab+6ab-9bc= | | 3x-16=4-2x | | 48s-34=48-28s | | 10-7=63 | | 51x-7=34x+163 | | .06x+x=5000 | | 3(4x)=27 | | 35-10= | | (x+5)(x+7)=105 | | sin(2x)=cos(5x) | | b^2-3=6 | | Y=9x-4xy+2x-xy | | 5r^2=10 | | 4y+20=15y-24 | | 3*ln(x+2)=9 | | 112+13p=86 | | 5x-16=x |